2022
DOI: 10.12657/denbio.088.006
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of site productivity for oak in Poland

Abstract: The site index (SI) is the most commonly used and representative measure of the phytocentric approach; it evaluates the site productivity based on the stand height and age. In the case of mixed stands with complex structures, phytocentric methods are very limited, while in non-forest areas, they are not ap­plicable. In situations where the applicability of phytocentric methods is limited, the site productivity is de­termined by geocentric methods. Geocentric methods allow direct modelling of site productivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Numerous studies have shown that growth modelling, especially on a regional scale, provides information for a more accurate assessment of forest growth and should be an important component of regional forest planning and management (Coops et al, 2007;Coops et al, 2010;Socha et al, 2020b). Variability in growth dynamics can lead to differences in height growth trajectories due to local variations in climate, soils and genotype-environment interactions (Viet et al, 2022). Thus, regional variation in growth trajectories can lead to inappropriate estimates of site productivity (Socha et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that growth modelling, especially on a regional scale, provides information for a more accurate assessment of forest growth and should be an important component of regional forest planning and management (Coops et al, 2007;Coops et al, 2010;Socha et al, 2020b). Variability in growth dynamics can lead to differences in height growth trajectories due to local variations in climate, soils and genotype-environment interactions (Viet et al, 2022). Thus, regional variation in growth trajectories can lead to inappropriate estimates of site productivity (Socha et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, evaluating these factors within a model is necessary (Zangiabadi et al, 2021). Normally, EVs, including climate, temperature, precipitation, soil pH, clay, sand, silt, bulk density, nitrogen in soil, soil organic carbon, topography, altitude, slope, and the normalized difference vegetation index (NDVI), are considered in species distribution (Dubuis et al, 2013;Oyebanji et al, 2021;Viet et al, 2022).…”
Section: Environmental Variablesmentioning
confidence: 99%
“…Forest ecosystems, which cover one-third of the world's land area and encompass more than 24.6 million square kilometers, are crucial for global ecosystem services and carbon cycling, particularly under the influence of climate change (Viet et al, 2022). These ecosystems, predominantly temperate and boreal forests, consist of diverse deciduous and coniferous trees that are well-adapted to a broad range of environmental conditions, especially in terms of temperature and precipitation (Tasenkevich et al, 2023).…”
Section: Introductionmentioning
confidence: 99%